The Role of School Management in Implementing the Pancasila Student Profile from the Perspective of Islamic Religious Education at MAN 9 Jakarta - Rohimah, Rohimah; Pudjiono, Pudjiono; Guntari, Dedeh (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia, 2023)
School management is the administration of a school in accordance with its predetermined vision and mission. School management plays a crucial role in enhancing the quality and achievements of the school. Therefore, this research aims to: 1) understand the implementation of school management; 2) determine the role of school management in implementing the student profile of Pancasila; 3) identify the challenges faced by school management in applying the perspective of Islamic education. In the context of the Merdeka curriculum, the study also seeks to explore the supporting and inhibiting factors, as well as the strengths and weaknesses perceived by teachers and students in the school. This research utilizes a descriptive qualitative approach based on observation, interviews, and documentation of the research subjects to obtain detailed information. The findings reveal that the implementation of the Pancasila Student Profile is not optimal due to various obstacles, leading to a lack of detailed information provided by educators. The research results indicate that the school management implemented is quite effective, encompassing learning management, student management, personnel management, facility management, financial management, community relations management, and special services management. The Pancasila Student Profile aims to shape Indonesian students into lifelong learners with global competence and behavior in accordance with Pancasila values, featuring six main characteristics: (1) faithful, devoted to God Almighty, and possessing noble character, (2) globally diverse, (3) collaborative, (4) independent, (5) critical thinking, and (6) creative.